Impact Evaluation on Improving Voluntary Medical Male Circumcision Demand in Malawi through the Use of Incentives - World Bank (World Bank, Washington, DC, 2018)
This report presents an impact evaluation assessing the effect of incentives on improving the uptake of Voluntary Medical Male Circumcision (VMMC) in two districts in Malawi. The cluster randomised control trial was led by the National AIDS Commission of Malawi and implemented from December 2015 to April 2016. The primary research question was whether incentives can increase VMMC uptake among in-school and out-of-school males aged 10-34. Collective incentives (e.g. whiteboards, football equipment) to schools and Mothers’ Groups, as well as individual incentives in the form of vouchers for VMMC were tested. The evaluation found that incentives in the form of vouchers for VMMC work. The vouchers had a significant positive impact on VMMC demand by increasing the odds of getting circumcised by over seven times. Secondary distribution by voucher recipients showed potential to informally increase distribution networks without increasing costs. There was some evidence of spill-over to relatives: nearly a third of participants in both study districts who had been given vouchers reported that they gave vouchers to relatives. Using the participants’ own social networks had the result of expanding the reach of the intervention without additional distribution costs. The evaluation also found that community-involvement, especially in the form of Mothers’ Groups, was essential to motivate young men to seek VMMC. The report discusses the policy implications of this positive finding of incentives.